2016
DOI: 10.11622/smedj.2015161
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of topical cyclosporine A 0.05% in vernal keratoconjunctivitis

Abstract: RESULTSAt baseline, the median values of the symptom and sign scores were 10.0 (range 5.0-18.0) and 6.0 (range 2.0-13.0), respectively. At Week 4 of treatment with topical CsA 0.05%, the median values of the symptom and sign scores were 3.0 (range 0-14.0) and 3.0 (range 0-8.0), respectively. The reductions in the symptom and sign scores were statistically significant. The reduction in the need for corticosteroid was statistically significant by Week 12 of therapy. No significant side effects were reported.CONC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 20 publications
2
23
0
Order By: Relevance
“… 24 , 25 More recent studies have shown even a dose of cyclosporine 0.05% 4 times per day may be effective in drug-resistant VKC in conjunction with topical corticosteroids. 26 …”
Section: Treatmentmentioning
confidence: 99%
“… 24 , 25 More recent studies have shown even a dose of cyclosporine 0.05% 4 times per day may be effective in drug-resistant VKC in conjunction with topical corticosteroids. 26 …”
Section: Treatmentmentioning
confidence: 99%
“…The presence of ethanol leads to patients' discomfort at product instillation, especially critical in pediatric patients. In addition, commercial ophthalmic products containing cyclosporine A at lower concentration (e.g., 0.5 mg/mL, Restasis ® ), are of dubious efficacy in the treatment of VKC [18] and they are highly expensive (e.g., cyclosporine 1.0 mg/mL, Ikervis ® ). In some cases, these preparations are not registered for the treatment of VKC or they are recognized as VKC orphan drug (e.g., cyclosporine 1.0 mg/mL, Verkazia ® ) [19,20], but still not commercially available or highly expensive.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Superior tarsal and limbal papillae, conjunctival hyperemia, and corneal involvement in the form of punctate epithelial keratitis, epithelial macroerosions, shield ulcers, plaque formation, and corneal neovascularization are also observed. [4] VKC can be described as IgE and T-cell mediated ocular allergic reaction with varied etiological factors comprising environmental allergens, climate, and genetic predisposition. [5] Mast cells, eosinophils, and their mediators play a major role in the clinical manifestation of the disease.…”
Section: Introductionmentioning
confidence: 99%